FINANCIAL FREEDOM: THE ROLE OF SUSTAINABLE CONSUMPTION AS A MEDIATOR OF FRUGAL LIVING - putri arliyanti, shilla; Fitri Astuti, Ratna; Puri Rahayu, Vitria; Haidar , Kadori (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Individuals will achieve financial freedom if they have adopted frugal living in their lives. The study aims to determine whether materialism and economic behavior have a direct and indirect effect on the frugal living of people in the city of Samarinda through the variable of sustainable consumption. The sampling technique used by researchers in the study was a non-probability sampling technique using the incidental sampling method with a sample size of 102 people. The data collection technique used by researchers is by distributing questionnaires. The data analysis used is the path analysis technique using the SmartPLS application. The results showed that people in Samarinda city have a good ability to invest, people do not spend time to have more goods and will use money to save or invest. The economic behavior of people in Samarinda city shows that good economic behavior makes people wise in making decisions to run life and manage finances by prioritizing needs over wants, so that frugal living can be achieved by managing finances wisely. These actions support the application of frugal living which makes people have a secure financial future.